Diplomasi Pertahanan Indonesia Dalam Pencapaian Keamanan Siber Melalui ADMM-Plus Tahun 2014-2019 - Samuel Mangara Sianturi (Neolectura, 2021)
Cyber ??security issues began to emerge along with advances in the field of information technology and the rapid increase in internet use. However, the greater the need for the internet in the daily activities of the world community, the more potential international security threats arise from activities within the cyber scope. Given the